DEVELOPMENT OF MANAGERIAL COMPETENCIES OF HEADS OF EDUCATIONAL INSTITUTIONS IN THE CONTEXT OF DIGITAL TRANSFORMATION AND INNOVATIVE CHANGES - Che Хiaodan; Adilgazy Akku; Shakirova Araily Dalelovna (Progress in Science, 2025)
In today's educational landscape, where digital technologies are rapidly evolving, educational institutions must adapt to these changes. This requires their leaders to be agile, innovative, and constantly improving their management skills. The digital transformation affects all aspects of educational organizations, from administrative management to the delivery of educational programs. It not only changes the way we interact but also demands a new level of professional competence from those in leadership positions. The significance of this research stems from the need to reevaluate the role of the educational institution's leader in the digital age. A contemporary leader is not merely an administrator, but also a visionary, motivator, and technological pioneer, capable of innovating and adapting the management framework to the evolving external and internal environment. The success of educational programs, the organization's adaptability, and the achievement of strategic objectives are all contingent upon the extent to which its managerial capabilities are developed. The objective of this research is to identify and theoretically substantiate effective strategies for enhancing the managerial capabilities of educational institution leaders in the context of digital transformation and innovative shifts. The novelty of this research lies in the creation of a holistic approach to the development of managerial skills, combining traditional and digital management methods. Additionally, we aim to clarify the structure of essential skills that are in demand in a digital educational environment.